Efeitos da radiação gama e do congelamento prévios à maturação na maciez da carne bovina - Rodrigues, Lorena Mendes (2017)
The objective of this study was to determine the effects of gamma radiation and freezing prior aging on Nellore beef tenderness. Samples of the Longissimus thoracis et lumborum were submitted for two treatments: refrigeration and freezing. The refrigerated (REFR) samples were irradiated (0, 3, 6 and 9 kGy) and aged (1 °C) for 1 and 14 days, while those of the freezing treatment (CONG) were first frozen (-18 ° C/ 24 hrs), irradiated, thawed (4 °C/ 24 hrs) and aged in the same way as the REFR samples. The interaction treatment x maturation time effect was observed for the pH factor. Frozen samples had significantly (P < 0.05) lower pH values. Aging increased the solubility of myofibrillar proteins (P < 0.05) at 14 days, whereas the sarcoplasmic proteins were more soluble in the REFR samples aged for 1 day. The purge was higher (P < 0.05) in CONG samples and in irradiated meat by doses of 6 and 9 kGy. However, the aging time for 14 days affected the purge, increasing its values. Cooking losses were affected by treatment and irradiation process, with higher values for irradiated samples and lower values for CONG samples. Gamma irradiation reduced (P < 0.05) the water holding capacity of the samples, while soluble collagen of samples irradiated at 9 kGy and sarcomere length of samples irradiated at 6 and 9 kGy were increased (P < 0.05). Higher (P < 0.05) miofibrilar fragmentation was observed in CONG samples, but samples irradiated at 3 and 6 kGy had lower (P < 0.05) values. In the CONG samples, the shear force was higher (P < 0.05) in those irradiated than in the control samples (0 kGy). However, the CONG and 14-days aged samples had (P < 0.05) the lowest values of shear force. Thus, it was concluded that gamma radiation did not overcome the problem of the inconsistency of bovine meat tenderness, but the freezing prior to aging proved to be helpful method to increase meat tenderness in bovine muscle.